2021
DOI: 10.1136/bmj.n189
|View full text |Cite
|
Sign up to set email alerts
|

Association between antihypertensive treatment and adverse events: systematic review and meta-analysis

Abstract: Objective To examine the association between antihypertensive treatment and specific adverse events. Design Systematic review and meta-analysis. Eligibility criteria Randomised controlled trials of adults receiving antihypertensives compared with placebo or no treatment, more antihypertensive drugs compared with fewer antihypertensive drugs, or higher blood pressure targets compared with lower targets. To av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
76
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(83 citation statements)
references
References 117 publications
(178 reference statements)
3
76
0
4
Order By: Relevance
“…4 Among the medications that lead to hyperkalemia, the most clinically important are RAAS inhibitors, which include angiotensin-converting-enzyme inhibitors, angiotensinreceptor blockers and mineralocorticoid receptor antagonists. [4][5][6] Although there is heterogeneity among studies, a systematic review and meta-analysis of 20 studies found that hyperkalemia is nearly twice as common (risk ratio 1.89, 95% confidence interval 1.56-2.30) in patients on drugs that act on the RAAS. 5 Moreover, data from clinical trials have also shown an increase in the incidence of hyperkalemia in patients with CKD or heart failure on RAAS inhibitor therapy.…”
Section: Who Is At Risk Of Hyperkalemia?mentioning
confidence: 99%
See 2 more Smart Citations
“…4 Among the medications that lead to hyperkalemia, the most clinically important are RAAS inhibitors, which include angiotensin-converting-enzyme inhibitors, angiotensinreceptor blockers and mineralocorticoid receptor antagonists. [4][5][6] Although there is heterogeneity among studies, a systematic review and meta-analysis of 20 studies found that hyperkalemia is nearly twice as common (risk ratio 1.89, 95% confidence interval 1.56-2.30) in patients on drugs that act on the RAAS. 5 Moreover, data from clinical trials have also shown an increase in the incidence of hyperkalemia in patients with CKD or heart failure on RAAS inhibitor therapy.…”
Section: Who Is At Risk Of Hyperkalemia?mentioning
confidence: 99%
“…[4][5][6] Although there is heterogeneity among studies, a systematic review and meta-analysis of 20 studies found that hyperkalemia is nearly twice as common (risk ratio 1.89, 95% confidence interval 1.56-2.30) in patients on drugs that act on the RAAS. 5 Moreover, data from clinical trials have also shown an increase in the incidence of hyperkalemia in patients with CKD or heart failure on RAAS inhibitor therapy. 12 An episode of hyperkalemia puts patients at risk of a second episode.…”
Section: Who Is At Risk Of Hyperkalemia?mentioning
confidence: 99%
See 1 more Smart Citation
“… 5 , 17 , 21 Furthermore, associated risks of RAAS drugs such as renal dysfunction, orthostatic hypotension, syncope, and polypharmacy are likely to be greater in older people. 22 …”
Section: Introductionmentioning
confidence: 99%
“…Ces patients pren nent généralement des inhibiteurs du système rénine-angio tensine-aldostérone (SRAA) pour réduire les risques d'aggravation de l'IRC et de complications cardiovasculaires 3 . Il arrive toutefois que ces médicaments déclenchent ou exa cerbent l'hyperkaliémie [4][5][6][7] . Certaines lignes directrices recom mandent désormais l'instauration de ces médicaments et l'augmentation de la posologie jusqu'à la dose maximale approuvée et tolérée par les patients afin d'optimiser l'issue cli nique 8,9 .…”
unclassified